Keterampilan Proses Sains (KPS) Siswa Melalui Asesmen Daring Menggunakan Analisis Model Rasch - Desy Fajar Priyayi; Dewi Rande Upa; Susanti Pudji Hastuti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to analyze students' science process skills through online assessments using the Rasch model analysis. The method used is quantitative through the analysis of the Rasch model. The data was collected using an online assessment with a test technique based on basic science process skills. The results showed that as many as 21 students (43.75%) had a KPS above or equal to the class average KPS and 12 students (25%) had high abilities in all aspects of basic KPS. In addition, as many as 27 students (56.25%) still have abilities below the class average and 15 (31.25%) still have abilities below the average test difficulty level. However, it can also be seen that 33 other students (68.75%) have a KPS ability above the average level of test difficulty. In conclusion, some basic process skills that need to be improved in students are observing, measuring, communicating and predicting skills. Keywords: Rasch Model Analysis, Online Assessment, Science Process Skills